Water polo coaches believe they gain an advantage by calling time-out before playing power-play, but is that really true? - Lupo, Corrado; Li Volsi, Damiano; Brustio, Paolo Riccardo; Ungureanu, Alexandru Nicolae (Frontiers in Psychology, 2025)
IntroductionThe present study aimed to evaluate the impact of time-out on power-play outcomes both in elite senior and youth matches and in relation to final (margin of victory, MoV) and current (margin of advantage, MoA) match scores (i.e., winning in unbalanced games, MW; winning-draw-losing in close games, W-D-L; losing in unbalanced games, ML).Materials and methodsA total of 97 (seniors, n = 50; youth, n = 47) European Championship matches were analyzed, comparing power-plays preceded or not by a time-out in relation to the following offensive indicators: goal, exclusion, penalty, and no-goal.ResultsThe results reported that both senior and youth levels have been characterized by better power-play outcomes without time-out (higher goals scored: senior, p ≤ 0.01, youth, p ≤ 0.001; and lower “no goal” events: p ≤ 0.01, youth, p ≤ 0.01). Similar trends were observed with respect to the MoV. Specifically, in senior close games, there were both significantly higher goals scored (p ≤ 0.05) and fewer ‘no goal’ events (p ≤ 0.05), and these patterns were also evident among youth losing teams in unbalanced games. Differently, for MoA, both higher goals scored (p ≤ 0.01) and lower “no goal” events (p ≤ 0.01) emerged for senior losing teams in unbalanced games and youth close games (higher goals scored, p ≤ 0.01; and lower “no goal” events, p ≤ 0.05).DiscussionTherefore, the present study demonstrated that time-out tends to limit the success of the following power-play action and that MoV and MoA approaches do not overlap. As a consequence, coaches could benefit from these findings by being more aware of the actual time-out consequences on the following power-play as well as their defensive potentialities when the opponents call time-out.